Post-natal development of EEG responses to noxious stimulation in pigs (Sus scrofa) aged 1-15 days - Kells NJ; Beausoleil NJ; Sutherland MA; Johnson CB (Ingenta on behalf of the Universities Federation for Animal Welfare (UFAW))
This study examined electroencephalographic (EEG) indices of acute nociception in pigs (Sus scrofa) aged 1, 5, 7, 10, 12 and 15 days, post-natal. Ten pigs per age were anaesthetised with halothane in oxygen and maintained at a light plane of anaesthesia. EEG was recorded bilaterally using a five-electrode montage. Following a 10-min baseline period, tails were docked using side-cutter pliers and recording continued for a further 5 min. Changes in the median frequency (F50), 95% spectral edge frequency (F95) and total power (PTOT) of the EEG were used to assess nociception. Tail-docking at one day of age induced no significant changes in the EEG spectrum. A typical nociceptive response, characterised by an increase in F50 and decrease in PTOT, was evident at ten days of age, with five and seven day old pigs exhibiting responses in either F50 or PTOT only. Pooling of data into ≤ 7 days of age and > 7 days of age revealed F50 was higher overall in the older group. Whilst PTOT decreased after docking in both groups, this response was larger and more prolonged in the older group. F95 increased after docking in the older pigs only. Overall, these data provide evidence of an increase in cortical responsiveness to noxious stimulation with increasing post-natal age, suggesting there may be qualitative differences in pain perception between age groups. Further, the data provide some support for current recommendations that tail-docking and other painful husbandry procedures be performed within seven days of birth in order to minimise their impact on animal welfare.
Keywords: animal welfare; EEG; nociception; pain; pig; tail-docking; 0608 Zoology; 0702 Animal Production; 0707 Veterinary Sciences